TEACHER’S DIFFICULTIES IN TEACHING SPEAKING USING AUDIO VISUAL AID FOR AUTISTIC STUDENTS - Acep Haryudin; Siti Ariani Jamilah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2018)
This article  was to identify and  to find out the teacher’s difficulties in teaching speaking to autistic student using audio visual. This research used descriptive design and qualitative research method. The instrument of the research are observation, interview and questionnaire about expressions of greetings. The data are collected by giving the teacher and autistic student interview, questionnaire and does observation and video recording. Additionally, the writer found that respondent’s difficulties in teaching speaking using audio visual aid for autistic student, divided into two sections: Internal; insecure and external that are 1) student; perform unique and unfamiliar character, deficit attention and concentrations, different of learning style, habit, and socialite with others, hard to produce and distinguish words with proper pronunciation, hard to perfect in pronunciation,  easily affected by their surroundings, using verbal and imagination in the way of learning. 2) Media; looking for a precise and compelling media, requiring a long time preparation. 3) Teaching process; should be interesting, should provide examples that are easy to understand, always tuck the material outside of school hours, need a lot of repetition, takes a long time. Additionally, it is recommended for further researchers to conduct similar studies in different contexts deeper.